2016
DOI: 10.1002/slct.201600524
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Biomolecular Interactions between Protein and Amino Acid Based‐Ionic Liquids: A Comparable Study between [Bmim][Br] and [Bmim][Gly] Ionic Liquids

Abstract: Protein is one of the most intricate and overriding biological system. Over the past years, there is an increased demand to consider ionic liquids (ILs) as novel biocompatible co-solvents for proteins.The overwhelming attention grabbed by new-generation ''amino acid ionic liquids (AAILs)''among various fields of modern chemistry and biology, has been attributed to their unique and designer nature. However, the stability of proteins in such AAILs is still untouched. Therefore, we have synthesized 1-butyl-3-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…Cho[Asp] revealed acceptable biocompatibility and on the other hand Cho [Trp] and Cho [Tyr] showed less biocompatibility towards all the tested bacteria. This is due to the presence of an aromatic ring in structure of the anion which leads to higher toxicity to the tested microorganism [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Cho[Asp] revealed acceptable biocompatibility and on the other hand Cho [Trp] and Cho [Tyr] showed less biocompatibility towards all the tested bacteria. This is due to the presence of an aromatic ring in structure of the anion which leads to higher toxicity to the tested microorganism [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant improvements in the catalytic activity of Cyt C was recorded by the authors 26,30,31. On the other hand, it has been suggested that the IL anion exerts a dominating effect on the catalytic activity and stability of enzymes 32. Recently, ILs based on anions derived from carboxylic acids and dicarboxylic acids with high hydrogen-bonding characteristics have been introduced in order to design protein friendly solvent systems 3338.…”
Section: Introductionmentioning
confidence: 99%
“…216,217 Cholinium ILs with different anions, for example amino acids, are emerging as a green and sustainable ionic liquid media for enzyme/protein stability and activity studies. 204,[217][218][219]220,221 Fatty acid [222][223][224][225] and lactam 226,227 based ionic liquids are also likely to significantly contribute towards the library of greener ILs for future industrial biocatalytic processes.…”
Section: Enzymes In Ionic Liquidsmentioning
confidence: 99%